Nutrition Status of Cancer Patients Attending Oncology Unit at Birat Medical College - Priyadarshini, Mona; Karki, Gyanendra Man Singh; Sapkota, Sulav (Birat Journal of Health Sciences, 2022)
Introduction: Malnutrition is a major problem in cancer patients which results in high morbidity and mortality. There are lack of comprehensive centers providing nutritional support to cancer patients in eastern region of Nepal. Objective: The objective of this study was to analyze the malnutrition status of cancer patients at Birat Medical College. It aimed to calculate the prevalence of malnutrition in cancer patients. Methodology: This descriptive cross sectional observational study of six months duration was conductedfrom 15th January 2021 to 15th July 2021 in the department of Oncology at Birat Medical College Teaching Hospital.All the histologically proven cancer patients during the study period were taken as study population whose body mass index were calculated. The relevant data were maintained inexcel sheet and analysis was done with the help of statistical software SPSS version22. Results: A total of 70 cases attended oncology unit during the study duration at Birat Medical College. The mean age of the cases were60 years (range 21-85) with the proportion of female patients almost equal(53%) to that of males. There was total 28 (40%) malnutrition cases out of which 22% were overweight,17% were underweight and only 1% obese. During the study period total 50% of the malnutrition cases were alive and 50% cases expired due to disease progression. Conclusion: Malnutrition is a major concern worldwide and even in cancer patients of Nepal. There is a need of comprehensive cancer center providing nutritional support to cancer patients in eastern region of Nepal.